2006
DOI: 10.1002/jez.a.349
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of immunocompetence by different androgen metabolites in a blenny with alternative reproductive tactics

Abstract: In Parablennius parvicornis, small reproductive males with relatively low expression of secondary sexual characters (MÀ morphotype) parasite on the parental investment of the larger nest-holder males which have fully developed secondary sexual characters (M1 morphotype). In comparison with M1 males, MÀ males have relatively low levels of androgens while having high blood cell percentages of lymphocytes and antigen responsiveness. Here we test the hypothesis that androgens are a causal factor for these differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
(53 reference statements)
2
12
0
Order By: Relevance
“…However, androgen levels (T and KT) did not show the expected negative correlation with lymphocyte percentages. Overall, these results are in agreement with data obtained from a related blenny species, the Azorean rock‐pool blenny, P. parvicornis (Ros et al. 2006a,b), suggesting that a trade‐off between androgen‐dependent traits (morphotype) and immunocompetence may be present at the level of ARTs in blennies which is not likely explained by acute immunosuppressive effects of circulating androgens.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…However, androgen levels (T and KT) did not show the expected negative correlation with lymphocyte percentages. Overall, these results are in agreement with data obtained from a related blenny species, the Azorean rock‐pool blenny, P. parvicornis (Ros et al. 2006a,b), suggesting that a trade‐off between androgen‐dependent traits (morphotype) and immunocompetence may be present at the level of ARTs in blennies which is not likely explained by acute immunosuppressive effects of circulating androgens.…”
Section: Discussionsupporting
confidence: 89%
“…Granulocytes were scarce and left out of analyses (in bourgeois males: less than 0.1% of total blood cell count). We report lymphocyte counts as percentages of the total cell count (lymphocytes + granulocytes + thrombocytes + erythrocytes, see Ros et al. 2006a,b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these inconsistencies, estrogens and estrogen-like endocrine disruptors appear to affect the balance of proliferation/apoptosis of lymphocytes. In contrast, androgens clearly exert an anti-proliferative effect on lymphocytes (Cook 1994;Slater and Schreck 1997;Saha et al 2004;Ros et al 2006) and affect IgM secretion (Hou et al 1999c;Saha et al 2004). Moreover, androgens are negatively correlated with plasma IgM during the reproductive cycle in rainbow trout (Suzuki et al 1997).…”
Section: Effects On Estrogens/androgens and Their Related Edcs On Immmentioning
confidence: 88%
“…However, there was no correlation between 11kT and immunity within each morphotype (Ros et al 2006a). Implant experiments indicated that the morphological effects are mediated by 11kT, whereas immunological effects seemed mediated by T, which led the authors to suggest that these effects might be decoupled in this species (Ros et al 2006b).…”
mentioning
confidence: 95%